Reduced SNAP‐25 alters short‐term plasticity at developing glutamatergic synapses. (4th June 2013) - Antonucci, Flavia; Corradini, Irene; Morini, Raffaella; Fossati, Giuliana; Menna, Elisabetta; Pozzi, Davide; Pacioni, Simone; Verderio, Claudia; Bacci, Alberto; Matteoli, Michela
Abstract : SNAP‐25 is a key component of the synaptic‐vesicle fusion machinery, involved in several psychiatric diseases including schizophrenia and ADHD. SNAP‐25 protein expression is lower in different brain areas of schizophrenic patients and in ADHD mouse models. How the reduced expression of SNAP‐25 alters the properties of synaptic transmission, leading to a pathological phenotype, is unknown. We show that, unexpectedly, halved SNAP‐25 levels at 13–14 DIV not only fail to impair synaptic transmission but instead enhance evoked glutamatergic neurotransmission. This effect is possibly dependent on presynaptic voltage‐gated calcium channel activity and is not accompanied by changes in spontaneous quantal events or in the pool of readily releasable synaptic vesicles. Notably, synapses of 13–14 DIV neurons with reduced SNAP‐25 expression show paired‐pulse depression as opposed to paired‐pulse facilitation occurring in their wild‐type counterparts. This phenotype disappears with synapse maturation. As alterations in short‐term plasticity represent a new mechanism contributing to cognitive impairments in intellectual disabilities, our data provide mechanistic clues for neuronal circuit alterations in psychiatric diseases characterized by reduced expression of SNAP‐25. Abstract : SNAP‐25, a key component of the synapse, is reduced in brain areas of schizophrenic patients. This study shows that SNAP‐25 levels alter short‐term plasticity, which might contribute to neural alterations in psychiatric diseases.